Escuela en casa: motivos y resultados - Chávez, Andrés (2017)
In the article, we are going to answer three questions: 1) Who and why do they choose to educate their children at home? 2) What are the social effects they have when studying at home? And 3) What are the academic results they get? In the text, will be speak of the homeschoolers and we refer to the children that by their parents’ decision they study at home instead of going to a school.